Premarital Medical Check-Ups in Islamic Marriage: A Maqasid al-Shariah Based Literature Review - Dani, Rahmat; Arisman, Arisman (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
Premarital medical check-ups represent a preventive strategy aimed at preparing couples for marriage and strengthening family well-being. However, in Indonesia, their implementation remains fragmented and insufficiently integrated into the formal marriage system. This study examines the role of premarital medical check-ups in safeguarding the objectives of Maqasid al-Shariah within Islamic marriage, as well as the challenges and opportunities surrounding their implementation. This study adopts a qualitative research design using a content analysis approach to examine scholarly sources, including journal articles, theses, and dissertations related to premarital health screening, Islamic law, and Maqasid al-Shariah.. Data were examined using content analysis to explore the relevance of premarital medical check-ups to the protection of life (hifz al-nafs), lineage (hifz al-nasl), intellect (hifz al-‘aql), wealth (hifz al-māl), and religion (hifz al-dīn). The findings indicate that premarital medical check-ups align closely with the objectives of Maqasid al-Shariah by reducing health risks, enhancing psychological and social readiness, and supporting sustainable family resilience. Nonetheless, regulatory gaps, limited public awareness, and cultural barriers continue to hinder their optimal implementation. This study proposes the integration of premarital medical check-ups with Maqasid al-Shariah based premarital guidance as a comprehensive approach to strengthening Islamic marriage systems in Indonesia.